2020
DOI: 10.3389/fspor.2020.00110
|View full text |Cite
|
Sign up to set email alerts
|

Psychological Flexibility Among Competitive Athletes: A Psychometric Investigation of a New Scale

Abstract: There is increasing interest in applying acceptance and mindfulness interventions among athletes. However, there is a lack of sport-specific psychometrically evaluated scales to measure the impact of these interventions. The present study describes the development of a measure: the Psychological Flexibility in Sport Scale (PFSS). Its validity was tested in two studies. In the first study, with 152 elite athletes from various sports, explorative factor analysis was used to evaluate the scale's validity, and one… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0
7

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 39 publications
2
10
0
7
Order By: Relevance
“…Intervention in this study was shown significant decrease aspects of psychological ill-being and significant increase aspects of psychological well-being, as well as level of mindfulness in a group of office workers (mean of BBQ was pre intervention 61.14 vs. post intervention 64.73), in comparing to a control group assigned to a waitlist condition (mean of BBQ was pre intervention 66.95 vs. post intervention 64.53). The BBQ has been used in several other studies and has shown satisfactory results in all of them [33][34][35][36][37] .…”
Section: Discussionmentioning
confidence: 99%
“…Intervention in this study was shown significant decrease aspects of psychological ill-being and significant increase aspects of psychological well-being, as well as level of mindfulness in a group of office workers (mean of BBQ was pre intervention 61.14 vs. post intervention 64.73), in comparing to a control group assigned to a waitlist condition (mean of BBQ was pre intervention 66.95 vs. post intervention 64.53). The BBQ has been used in several other studies and has shown satisfactory results in all of them [33][34][35][36][37] .…”
Section: Discussionmentioning
confidence: 99%
“…From a theoretical standpoint, this study significantly boosts the existing evidence for ACT-based intervention in performance enhancement, as its sample size was larger than those of the previous single-sample studies focusing on performance enhancement in non-medical populations [10][11][12][13]. This is hence the first documented case in the literature looking at the efficacy of ACT-based intervention for medical student-related performance anxiety.…”
Section: Discussionmentioning
confidence: 83%
“…There are existing interventions that share similar concepts with ACT per se, including the Mindfulness Acceptance and Commitment (MAC) protocol [9] for increasing "flow" [10] and the Mindfulness Sports Performance Enhancement (MSPE) protocol [11,12]. There is substantive evidence that such transdiagnostic mindfulness-based therapies are efficacious, even for one intervention, in terms of boosting performance by increasing psychological flexibility [13]. Some of the fields that have benefited from this include springboard diving [14], tennis [15], basketball [16], and weightlifting [17].…”
Section: Introductionmentioning
confidence: 99%
“…In sport, multiple studies have found benefits of mindfulness and acceptance interventions for athletes' performance (Bühlmayer, Birrer, Röthlin, Faude, & Donath, 2017;Lundgren et al, 2020;Noetel, Ciarrochi, Van Zanden, & Lonsdale, 2017). Furthermore, Birrer, Röthlin and Gareh's (2021) mini-review suggested that acceptance-based interventions can enhance athletes' wellbeing in sport.…”
Section: Acceptance and Commitment Therapymentioning
confidence: 99%
“…Psychological flexibility was measured using the Psychological Flexibility in Sport Scale (PFSS; Johles et al 2020). PFSS consists of seven questions and measures the extent to which participants avoid distressing thoughts, emotions, behaviors, or memories.…”
Section: Psychological Flexibilitymentioning
confidence: 99%